TWO NEW FRAGMENTS OF ANAXANDRIDES IN HESYCHIUS?. (2nd May 2018) - Dale, Alexander
Abstract : We can first note the obvious, that both glosses are sexual in nature: τὸ βιάζεσθαι γυναῖκας, 'to rape women'; in τὸ παιδὶ συνεῖναι we obviously have the euphemistic use of συνεῖναι, 'to have sex with a child'. Hesychius' entries have the appearance of straightforward dialect glosses, yet Ambraciot never elicited much attention in ancient dialectology and glossography. Furthermore, as ancient glossography consisted mainly in culling unusual vocabulary from literary texts, we can legitimately ask what sources might have been available to Hellenistic scholars for Ambraciot.